2021
DOI: 10.1021/acsapm.1c01076
|View full text |Cite
|
Sign up to set email alerts
|

Moisturized Polyacrylonitrile Copolymer for Stronger Precursor Fibers

Abstract: Polyacrylonitrile–methyl acrylate (PAN–MA) copolymers have been used as precursor materials for carbon fibers due to their excellent properties for developing carbonaceous microstructures during thermal treatment. High electron density in the acrylate part of the MA polymer is mainly responsible for the hygroscopicity of the copolymer. Adsorbed water can affect microstructures and material properties of precursor fibers. This study investigated the role of adsorbed water in precursor fibers prepared by convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…P (AN-MA) precursor fibers were manufactured through spinning, washing, and stretching processes. A dope solution with a concentration of 25 wt% was prepared and spun, as suggested in previous fiber spinning research [8,22]. DMSO was used for both the dope solvent and the coagulation bath, and the fiber formation conditions were controlled using distilled water and DMSO at a ratio of 1:1 for the coagulation bath.…”
Section: Fiber Spinning and Drawingmentioning
confidence: 99%
See 1 more Smart Citation
“…P (AN-MA) precursor fibers were manufactured through spinning, washing, and stretching processes. A dope solution with a concentration of 25 wt% was prepared and spun, as suggested in previous fiber spinning research [8,22]. DMSO was used for both the dope solvent and the coagulation bath, and the fiber formation conditions were controlled using distilled water and DMSO at a ratio of 1:1 for the coagulation bath.…”
Section: Fiber Spinning and Drawingmentioning
confidence: 99%
“…PAN homopolymer alone is not well manufactured into fiber due to limitations concerning spinnability and thermal stability, and therefore, research on various copolymers has been conducted [4][5][6]. Methyl acrylate (MA) is the material most often used to improve the spinnability and processability of PAN materials and is considered an essential copolymer material [7,8]. In addition, various copolymers, including acids, are used for stability in oxidation and carbonization processes, and MA and itaconic acid (IA) are used in the manufacturing of commercial carbon fibers [9].…”
Section: Introductionmentioning
confidence: 99%
“…30 High-quality precursor fibers have a positive effect on achieving highperformance carbon fibers. 7,31 Wet spinning and dry-jet wet spinning are the commonly adopted spinning methods for producing PAN precursor fibers. 32 Unlike wet spinning, in the process of dry-jet wet spinning, the filaments undergo partial gelation as they pass through an air gap before entering the coagulation bath.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fiber, due to its excellent characteristics of lightweight and high strength, is widely used in lightweight composite materials and plays an irreplaceable role in the fields of national defense, military industry, aerospace, and sports equipment. Carbon fiber is prepared through thermal stabilization and carbonization of precursor fibers, , with over 90% of commercial carbon fibers still using polyacrylonitrile (PAN) as the precursor material, although many studies have attempted to use other polymers with linear or cyclic structures to prepare carbon fibers. Numerous researchers have also been exploring the structure–property relationships of carbon fibers in an attempt to develop high-performance carbon fibers that are increasingly close to theoretical strength and modulus. , Li et al found that the microcrystal size increased with the increase in fiber strength; the size of the micropore also increased, but its quantity decreased . Hao et al analyzed the effect of the microcrystal structure and preferred orientation of different grades of commercial carbon fibers on tensile modulus and found that the tensile modulus of carbon fiber decreased gradually with increasing interlayer spacing and orientation angle, while it rose with the increase of microcrystal size.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] ACFs possess narrowly distributed stomata along the outer surface toward the interior, which own higher adsorption-desorption kinetics and lower diffusion resistance than other powdered or granular-activated carbon substances. [7,8] Generally, the organic precursor for ACFs mainly includes polyacrylonitrile fibers, [9,10] nitrile fibers, [11] asphalt fibers, [12,13] viscose fibers [14,15] and phenolic fibers. [16][17][18] Among them, viscose fibers have become the most popular organic precursor material for the preparation of ACFs due to the low price and abundant resources.…”
Section: Introductionmentioning
confidence: 99%